Da lousa ao palco: teatro como possibilidade de desenvolvimento de agência - Salvador, Francisca Nunes da Mota (2014)
The aim of this research is to investigate, critically, the development of creative agency in chain activity system on a drama project for teenagers at elementary school (7th grade). The project is developed at Instituto Dinâmico Alfredo Chaves (ES), where proposals aimed at reading and production of speech genres for elementary and high school are promoted. The question that organizes this research is: How do chain activity system enable the development of agency? Two sub questions were proposed: What types of collaboration were constituted in the meetings? What types of agency flourished? This study finds itself within the context of Applied Linguistics and is supported by the Social Historical and Cultural Activity Theory, with focus on agency. It is designed as a Critical Research on Collaboration (MAGALHÃES, 2010; 2011), whose goal is to create the context of negotiation in which the subjects learn from each other, generating shared knowledge. The corpus of this research consisted of four meetings held during the process of production of a play as well as testimonials, written by the students who were involved in the project in the year of 2013. Data were analyzed prioritizing enunciation, discursive and linguistic aspects, based on studies on argumentation. The results show that the process, which was carried out by the subjects of research, promotes collaborative relationships, enabling the development of agency. However, it is important that the teacher acts intentionally and responsively so that there is critical collaboration in a way that subjects take part in relational and transformative agency